One’s trash is someone else’s treasure: sequence read archives from Lepidoptera genomes provide material for genome reconstruction of their endosymbionts - Victoria G. Twort; Daniel Blande; Anne Duplouy (BMC Microbiology, 2022)
Abstract Background Maternally inherited bacterial symbionts are extremely widespread in insects. They owe their success to their ability to promote their own transmission through various manipulations of their hosts’ life-histories. Many symbionts however very often go undetected. Consequently, we have only a restricted idea of the true symbiont diversity in insects, which may hinder our understanding of even bigger questions in the field such as the evolution or establishment of symbiosis. Results In this study, we screened publicly available Lepidoptera genomic material for two of the most common insect endosymbionts, namely Wolbachia and Spiroplasma, in 1904 entries, encompassing 106 distinct species. We compared the performance of two screening software, Kraken2 and MetaPhlAn2, to identify the bacterial infections and using a baiting approach we reconstruct endosymbiont genome assemblies. Of the 106 species screened, 20 (19%) and nine (8.5%) were found to be infected with either Wolbachia or Spiroplasma, respectively. Construction of partial symbiotic genomes and phylogenetic analyses suggested the Wolbachia strains from the supergroup B were the most prevalent type of symbionts, while Spiroplasma infections were scarce in the Lepidoptera species screened here. Conclusions Our results indicate that many of the host-symbiont associations remain largely unexplored, with the majority of associations we identify never being recorded before. This highlights the usefulness of public databases to explore the hidden diversity of symbiotic entities, allowing the development of hypotheses regarding host-symbiont associations. The ever-expanding genomic databases provide a diverse databank from which one can characterize and explore the true diversity of symbiotic entities.